القيود الواردة على الملكية العقارية والمتعلقة بالموارد المائية - شيبات, سارة (جامعة الوادي University of Eloued, 2017)
تندرج الحقوق الواردة على الموارد المائية ضمن القيود التي ترد على الملكية العقارية؛ فقد تتقيد هذه الأخيرة حماية للمصلحة العامة للدولة التي تنفرد بملكية الموارد المائية كما قد تتقيد حماية لحق الأفراد أو الخواص في الانتفاع بالمياه. Abstract: The rights related to water resources are one of the limits attributed to land property that can be limited in order to protect public interests in the state which is the only owner of the water resources. It can also be limited in order to protect individuals rights of water utilization.
Keywords: الموارد المائية؛ حق الملكية؛ الرخصة؛ الامتياز؛ الارتفاقات الإدارية؛ حق المجرى؛ حق المسيل